Climate Change and Mental Health: Exploring the Psychological Impacts of Environmental Distress in Indonesia - Najmah Shareeff; Rini Kuswohadi Pramono; Arsan Saliha (Scientia Psychiatrica, 2024)
Introduction: Climate change is a global crisis with profound implications for mental health. Indonesia, as a highly vulnerable country, faces escalating environmental challenges that can significantly impact the psychological well-being of its population. This study investigates the psychological impacts of environmental distress related to climate change in Indonesia. Methods: A mixed-methods approach was employed, combining quantitative and qualitative data collection. A cross-sectional survey was conducted with a representative sample of 1,500 Indonesian adults to assess the prevalence of mental health issues associated with climate change concerns and experiences. Qualitative data were gathered through in-depth interviews with 50 individuals from diverse backgrounds who reported experiencing significant environmental distress. Results: Quantitative analysis revealed a strong correlation between climate change concerns and various mental health problems, including anxiety, depression, and post-traumatic stress disorder (PTSD). Individuals directly affected by extreme weather events exhibited higher levels of psychological distress. Qualitative findings highlighted the complex interplay of factors contributing to environmental distress, including fear of future impacts, loss of livelihoods, displacement, and cultural disruption. Conclusion: Climate change poses a significant threat to mental health in Indonesia. The findings underscore the urgent need for comprehensive mental health support services and community-based interventions to address the psychological impacts of environmental distress. Further research is needed to explore the long-term effects of climate change on mental health and develop culturally appropriate coping strategies.